HUBUNGAN DUKUNGAN SOSIAL DENGAN PENYESUAIN DIRI SISWA BROKEN HOME DI SMKN 4 PADANG SEMESTER GENAP TAHUN AJARAN 2025/2026 - Novita Yulia Nengsih; Linda Fitria; Ridho Rismi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Novita Yulia Nengsih, “The Relationship between Social Support and the Adjustment of Broken Home Students at SMK Negeri 4 Padang, Even Semester of the 2025/2026 Academic Year”, Undergraduate Thesis, Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Putra Indonesia University "YPTK" Padang. His study aims to determine the relationship between social support and the adjustment of broken home students at SMK Negeri 4 Padang during the even semester of the 2025/2026 academic year. The research employed a quantitative approach with a simple random sampling technique. The sample consisted of 60 students from a total population of 207 students. The instruments used for data analysis were SPSS 24 and Microsoft Excel 2016. Based on the research findings, the calculated t-value was greater than the t-table value, namely 0.218 > 0.254 with a significance level of α = 0.05. Therefore, the hypothesis was accepted, indicating a significant relationship between social support and the adjustment of broken home students in grade 11 at SMK Negeri 4 Padang. The coefficient of determination showed that social support contributed 4% to students' adjustment. This suggests that students who receive high levels of social support tend to be better at managing their personal adjustment.